Digestibilidad del polen de cactáceas columnares en los murciélagos glosofaginos Glossophaga longirostris y Leptonycteris curasoae(Chiroptera: Phyllostomidae) - Muñoz-Romo, Mariana (2005)
We examined the protoplasmic assimilation of columnar cacti pollen grains in two species of Venezuelan desert glosophagine bats, Glossophaga longirostrisand Leptonycteris curasoae, by determining the amount of empty (digested) pollen grains found in their fecal samples. To determine the amount of empty pollen grains, the fecal samples were stained to differ between empty and full (non-digested) pollen grains. The number of empty and full pollen grains observed in the fecal samples were corrected using the amount of aborted pollens present (before anthesis) in flowers of the columnar cacti species (Subpilocereus repandus, Stenocereus griseus and Pilosocereus tillianus) used by bats as food in the study site; G. longirostris and L. curasoae digested 64.2% and 71.3% of all the pollens fed, respectively. These high values confirm the importance of pollen in the diet of these bats, given its high nitrogen level.